Emotional Intelligence of Students at Public Elementary Schools in Pegasing District - Marwan, Marwan; Syahrin, Alfi; Muharramsyah, Rambang (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to describe the emotional intelligence of students in state elementary schools in Pegasing District. The type of research is quantitative descriptive. The research population was 106 class V students of public elementary schools in gugus 2 Pegasing District. The sampling technique used the Slovin formula with a total sample of 84 students. Research data collection techniques use observation, questionnaires and documentation. The data analysis technique uses percentage analysis. The research results show that students' emotional intelligence is classified as good, this result is seen from several aspects; first, self-intelligence 83.40% good category, second, self-control 83.90% good category, third, self-motivation 83.88% good category, fourth, empathy 85.1% category, good, five, social skills 84 % good category.